Evaluation of thin film nanocomposite membrane incorporated with carbon-based quantum dots - Seow, Eric Kai Jun (2021)
Water crisis is a severe global matter. In order to mitigate this matter, filtration with conventional polymeric membrane have been developed as it offers great flexibility, accessibility, and is cost-effective. However, conventional filtration membranes suffer from limitations such as membrane fouling. In this study, the fabrication method, characteristic and performance of carbon-based quantum dots incorporated thin film nanocomposite (TFN) nanofiltration (NF) and reverse osmosis (RO) membranes from previous works were evaluated. The carbon-based quantum dots included in this review are carbon quantum dots, graphene quantum dots and graphene oxide quantum dots. The introduction of functionalized carbon-quantum dots was found to have significant effect on the membrane characteristic and performance. The studies showed good compatibility of the quantum dots with a wide variety of amine and acyl chloride monomers. In addition, carbon-based quantum dots had significant effects on the membrane characteristics. The surface roughness was inconsistent across the reviewed journals mainly due to the difference of the size of the quantum dot. Besides, oxygen-containing functional groups were observed after the introduction of carbon-based quantum dots which indicated the improved hydrophilicity. The membrane flux was improved significantly ranging from 1.5 to 6.8 times with a little amount of carbon-based quantum dots. Furthermore, the addition of carbon-based quantum dots into the PA matrix also helped to overcome the conventional limitation of filtration membrane, which is membrane fouling. Moreover, the surface charge of the membranes also increased which enhanced the membrane antifouling properties. All in all, it shows that carbon-based quantum dots are suitable to be incorporated into TFN membranes in terms of filtration performance, regardless of the type of filtration process. Nevertheless, most of the previous studies included in this work are limited to laboratory scale, where the consideration for industrial application such as the large-scale synthesis of carbon-based quantum dots and fabrication of TFN membranes, as well as the maintainability of the membrane have not been investigated fully.